Salmonella-induced pulmonary and pericardial abscesses in a patient presenting with subacute cough. (2022) - Ismail, S.; Thomas, M.; Razok, Almurtada; Akbar, R.; Abid, Fatma Ben; Wilson, Godwin
Abstract: The non-typhoid Salmonella (NTS) species are commonly associated with gastroenteritis and other forms of intestinal disease. Thoraco-pulmonary infections are less commonly reported. We describe the case of a 66-year-old Qatari lady who presented with subacute cough. Chest imaging revealed multiple pulmonary and a pericardial cavitary lesion with air fluid levels. Bronchoalveolar lavage culture grew Salmonella species group D. The patient was treated with 4 weeks of appropriate antibiotics. Clinical and radiological improvement were documented on subsequent follow up. To our knowledge, this is the first reported case of pulmonary and pericardial salmonella abscesses in the state of Qatar.